ANALYSIS OF ENGINEERING CREW COMPETENCIES REGARDING THE USE OF FIRE EXTINGUISHERS IN THE ENGINE ROOM OF THE KM. TATAMAILAU - Adjie Chrisyono Boru; Ahmad Wahid; Hasiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the competence of engine crew members in the use of firefighting equipment during fire drills in the engine room of KM. Tatamailau and to identify the supporting and inhibiting factors affecting its implementation. The research employed a descriptive qualitative method with data collected through observation, interviews, and documentation. The results indicate that the competence of the engine crew in operating the hydrant system is categorized as fairly good, as reflected in their knowledge, skills, and work attitudes. The crew members were able to perform the basic procedures for operating the hydrant system in accordance with established procedures. However, several obstacles were identified, including suboptimal coordination among crew members and a lack of familiarity with emergency equipment. Supporting factors include the availability of firefighting equipment, the implementation of safety procedures, and regular training exercises. Therefore, improvements in training and crew coordination are necessary to enhance the effectiveness of fire emergency response in the engine room.